(untitled) (Revista Apotheke, 2021)
Rubem Valentim’s emblems and objects move between art and religion, composing a symbolic-magical repertoire in geometric aesthetic works that dialogue with Afro-Brazilian religiosity. Impregnated by popular syncretism, the artist in his displacements composes a collection of symbols rooted in the primitive, prospecting themes that are debated in contemporary art. The experiences and meanings of candomblé are observed in the Nago ritualistics and encantaria (in English can be defined as supernatural entities, spirits) in an interview with the priest of the Ilê Asè Aféfé t’Oyá temple. This qualitative research goes through the works of Rubem Valentim establishing relationships with the practices of the temple and literature, presenting the existence and the meaning of tradition and encantaria in a temple located in the city of Chapecó, Santa Catarina. With unique characteristics, full of signs and meanings, the temples are spaces of preservation, re-signification, and resistance of culture, allowing ethnic survival and the continuity of the mythical African universe. Because of their transcendent force and energy, they are configured as spaces of permanent struggle against racism, discrimination, and intolerance. The art inside the temple’s space carries identities and connects subjectivities.